Pengembangan Media Pembelajaran Berbasis Web (Google Sites) untuk Meningkatkan Keterampilan Berpikir Kritis dan Literasi Digital Siswa Kelas V Sekolah Dasar - Dewi Setianingsih; Siswono, Tatag Yuli Eko; Yumiati (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The increasing use of the internet as a learning resource in the 21st century makes digital literacy important for students to have in addition to critical thinking skills. It is necessary to develop technology-based learning media to support improving critical thinking skills and digital literacy. This research aims to describe the process and results of developing valid, practical, and effective web-based (Google Sites) learning media to improve students' critical thinking skills and digital literacy, describe student activities, and analyze the increase in students' critical thinking skills and digital literacy after using media. This research is development research that refers to the ADDIE development model. The data sources were teachers and fifth grade students at SD Muhammadiyah 8 Surabaya. Data collection procedures use interview, validation, observation, questionnaire and test methods. The data analysis method uses qualitative and quantitative descriptive techniques. The development of web-based (Google Sites) learning media which was carried out in 5 stages namely analysis, design, development, implementation, and evaluation, produced media with the criteria of being very feasible, very practical and effective for use in learning fraction arithmetic operations. Student activities in learning are categorized as very active and there is a significant increase in students' critical thinking skills with an average N-Gain score of 0.52 (medium), as well as an increase in students' digital literacy with an average N-Gain score of 0.56 (medium).